Spatio-Temporal analysis of Child Marriage Recorded in the Iran Counties (The case study; Marriage data of the National Organization for Civil Registration; 2016 ~ 2021) - Ali Goli; Zohreh Savab; Yaser Dorzadeh (مطالعات اجتماعی روان‌شناختی زنان, 2025)
Early marriage or child marriage(CM) is a pervasive global issue. An examination of global data indicates an average of 19% prevalence of this phenomenon across various countries in 2023. According to the latest statistical yearbook of the Civil Registration Organization in 2022, over 14.5% of registered marriages occurred at ages below 18, with this figure exceeding 27% for girls and approximately 2% for boys.The present study investigates the temporal-spatial changes in CM across Iranian counties from 2016 to 2021. This research adopts a quantitative approach and is characterized by secondary analysis. The statistical population comprises the counties of Iran, and data analysis was conducted using GIS and spatial statistical methods. The spatial correlation index was utilized to assess spatial distribution and identify the most significant hubs, The time-space cube model was employed to estimate the percentage of CR in 2025.Findings revealed that during the years 2016-2021, Semnan and Qazvin provinces exhibited the lowest percentages of CM, Whereas Sistan and Baluchestan, Khuzestan, Ardabil, and Razavi Khorasan provinces emerged as the primary hubs of CM. In the eastern and northwestern regions,CM among girls showed an increasing trend, while among boys in the eastern areas, a complete upward trend was observed from the northeastern to the southeastern regions, with a similar increasing trend noted in the northwestern parts. The spatial pattern analysis of CM indicated two distinct distributions between boys and girls, and the 2025 estimates suggest an increase in this occurrence among girls in the current CM hubs.